ISOLATION AND CHARACTERIZATION OF SYMBIOTIC BACTERIA FROM THE MIDGUT OF NATURAL POPULATION OF Drosophila ananassae. - PRIYANKA MAJI; CHANDRASEKHAR CHAKRABARTI; SOUMENDRANATH CHATTERJEE (International Journal of Pharma and Bio Sciences, 2013)
Natural population of Drosophila ananassae flies were captured from the locality of Burdwan (West Bengal, India) and were cultured under aseptic conditions. Midguts of the third instar larvae were dissected under a binocular microscope in laminar air flow for the isolation of the bacteria. The phenotyping, biochemical and 16S rRNA phylogeny identified the most prevalent bacteria as Paenibacillus nanensis P012 (JQ782427) and Bacillus cereus P013 (JQ782428) which was obtained all through the year. Both the bacteria were gram negative, spore forming, rod shaped, showed positive result for catalase, methyl red test, nitrate reduction, oxidase test, urease test but negative for indole production, Vogues-Proskauer test and starch hydrolysis. The antibiotic tetracycline (30µg), doxycycline hydrochloride (30µg), gatifloxacin (5µg), ofloxacin (5µg), levofloxacin(5µg) are sensitive and ampicillin(10µg), chloramphenicol (30µg) showed resistant by antibiotic sensitivity test. Phylogenetic affiliation of the bacteria (P012 and P013) was done by 16S rRNA gene sequence analysis and phylogenetic tree was constructed through multiple sequence alignments followed by a neighbor-joining analysis.